Предмет: Алгебра,
автор: HopiTakeo
Решить уравнение
Ответы
Автор ответа:
1
3z² + (6 + 7i)z + 7i = 0
а дискриминанты никто не отменял }}}}}}}
D = b² - 4ac = (6 + 7i)² - 4*3*7i = 6² + 84i + (7i)² - 84i = 36 - 49 = -13
z12 = (-b +- √D)/2a
b = 6 + 7i
a = 3
√D = i√13
z12 = (-(6 + 7i) +- i√13)/6 = (-6 - 7i +- i√13)/6 = (-6 - i(7 -+ i√13))/6
z1 = -1 - i(7 + √13)/6
z2 = -1 - i(7 - √13)/6
HopiTakeo:
тогда должно получится (+-6 +- i(7-√13))/6
-6/6 = -1
Похожие вопросы
Предмет: География,
автор: Аноним
Предмет: Химия,
автор: dima2979
Предмет: Українська література,
автор: justmailuser228
Предмет: Биология,
автор: ароморфоз
Предмет: Музыка,
автор: rpaqrj